Relief carving of a peacock - Temples of India Project Team (Jio Institute, 2024)
Broken debris from the original temple assembled on the south face of the adhisthana. Relief carvings of geometric, flora and fauna motifs feature all around the adhisthana. Seen here is a relief carving of a peacock.